O acompanhante na instituição hospitalar : relatos de uma experiência - Dibai, Márcia Bárbara Souza (2005)
The present study had as objective to know, from the family companion perception, their experience in accompanying the hospitalized adult patient. It is an exploratory and descriptive study, based on the qualitative approach and case study example, which was carried out in the medical clinic department of a hospital-school. It was used the sample by saturation, being interviewed 12 family companions. It was also opted to obtain data from 8 professionals from the hospital, in order to better understand the study object. As a methodology of data collection, semi-structured interviews were realized and the data were treated by the content analysis technique (BARDIN, 1977). The results showed that affectivity and obligation were the main reasons that led the companions to stay with the hospitalized relatives. During the stay in the hospital, the companions realized more self-care activities that had as objective to supply the patient s basic needs of nutrition, hydration, elimination, hygiene, rest-activity and comfort. The most perceived difficulties by them were related to personal questions and the infra-structure of the hospital, that imply the necessity to offer a better comfort for their permanence with the interned patient. The difficulties related to interaction with the staff, as well as the activities that they realized were less noticed. During the accompanying period, physical alterations were identified, with weariness predominance, and emotional alterations, in which preoccupation permeated all the process, also being manifested other feelings like sadness, nervousness, fear, insecurity, fragility and loneliness. In relation to the alterations occurred in the daily life, the most cited by the family companions were to abandon the house, interrupt the household chores, as well as not to give attention to children. Faith was recognized by them as the main confrontation strategy for the overcoming of the difficulties found in the hospital context. The experience narrated by the companions reveals their objective demands as well as the subjective, and shows the necessity to create a service policy to this specific group, bringing implication to the hospital institution and the staff.